2020
DOI: 10.1002/cbf.3495
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non‐coding RNA Gm10804 suppresses disorders of hepatic glucose and lipid metabolism in diabetes with non‐alcoholic fatty liver disease

Abstract: Deregulated glucose and lipid metabolism are the primary underlying manifestations associated with diabetes mellitus (DM) and non-alcoholic fatty liver disease (NAFLD). This study aims to investigate the role of Gm10804, a novel long noncoding RNA (lncRNA), in regulating hepatic glucose and lipid metabolism in DM complicated with NAFLD (DM-NAFLD). Mouse primary hepatocytes exposed to high glucose (HG) were used as a cell model. A mouse DM-NAFLD model was established by high-energy feeding combined with intrape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The second lncRNA with the highest number of mRNA targets, the TBT-downregulated Gm10804. Recently, Li and colleagues [ 36 ] reported that low expression of Gm10804 improves glucose and lipid metabolism disorders in hepatocytes from mice exposed to high glucose, which is of importance as the liver plays a key role in adjusting glucose levels, in turn affecting energy homeostasis in other tissues [ 37 ]. One of the correlated target mRNAs of this lncRNA is the TBT-downregulated Slc27a2 mRNA, also known as FATP2 .…”
Section: Discussionmentioning
confidence: 99%
“…The second lncRNA with the highest number of mRNA targets, the TBT-downregulated Gm10804. Recently, Li and colleagues [ 36 ] reported that low expression of Gm10804 improves glucose and lipid metabolism disorders in hepatocytes from mice exposed to high glucose, which is of importance as the liver plays a key role in adjusting glucose levels, in turn affecting energy homeostasis in other tissues [ 37 ]. One of the correlated target mRNAs of this lncRNA is the TBT-downregulated Slc27a2 mRNA, also known as FATP2 .…”
Section: Discussionmentioning
confidence: 99%
“…T2DM is a metabolic disorder whose pathogenesis involves the interaction of multiple genes and aspects. 35 The target organ of insulin is the liver, which plays a critical role in maintaining the homeostasis of glucose metabolism. Recent studies have shown that the up- or downregulation of mRNA transcription and protein expression levels of some related genes in the liver glucose metabolism pathway can result in higher FBG and OGTT levels, and eventually lead to diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic gluconeogenesis can maintain the glucose and lipid of cellular or whole-body in a steady state, so it plays a vital part in hepatic glucose metabolism (Gastaldelli et al, 2000;Wu et al, 2018). Convincing evidence indicates that overactivated hepatic gluconeogenesis and lipogenesis contribute to the pathogenesis of metabolic disorders, including DM and NAFLD (Cui et al, 2018;Dong et al, 2019;Li et al, 2020). Therefore, one of the important targets in the treatment of T2DM-NAFLD is to inhibit the glycolipid toxicity caused by gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%